Construction of an Artificial Biosynthetic Pathway for the Styrylpyrone Compound 11-Methoxy-Bisnoryangonin Produced in Engineered Escherichia coli - Heo, Kyung Taek; Lee, Byeongsan; Jang, Jae-Hyuk; Ahn, Jung-Oh; Hong, Young-Soo (Frontiers in Microbiology, 2021)
A cDNA clone (named pnpks), which shows high homology to the known chalcone synthase (CHS)-like type III PKS, was obtained from the leaves of Piper nigrum. The PnPKS protein with ferulic acid catalyzed lactonization instead of chalcone or stilbene formation. The new product was characterized as a styrylpyrone, 11-methoxy-bisnoryangonin, which is the lactonization compound of a linear triketide formed as the reaction product of PnPKS protein with ferulic acid. These results show that pnpks encodes a styrylpyrone synthase (SPS)-like PKS that catalyzes two-chain elongation with feruloyl CoA-linked starter substrates. Although these styrylpyrone compounds are promising for use in human healthcare, they are mainly obtained by extraction from raw plant or mushroom sources. For de novo synthesis of 11-methoxy-bisnoryangonin in the heterologous host Escherichia coli from a simple sugar as a starter, the artificial biosynthetic pathway contained five genes: optal, sam5, com, and 4cl2nt, along with the pnpks gene. The engineered L-tyrosine overproducing E. coli ∆COS1 strain, in which five biosynthetic genes were cloned into two vectors, pET-opT5M and pET22-4P, was cultured for 24 h in a minimal glucose medium containing ampicillin and kanamycin. As a result, 11-methoxy-bisnoryangonin production of up to 52.8 mg/L was achieved, which is approximately 8.5-fold higher than that in the parental E. coli strain harboring a plasmid for 11-methoxy-bisnoryangonin biosynthesis. As a potential styrylpyrone compound, 11-methoxy-bisnoryangonin, was successfully produced in E. coli from a simple glucose medium, and its production titer was also increased using engineered strains. This study provides a useful reference for establishing the biological manufacture of styrylpyrone compounds.